Macroparticles in beam-plasma systems - Bizyukov, A.A.; Girka, I.O.; Romashchenko, E.V.; Chibisov, O.D. (Вопросы атомной науки и техники, 2016)
The macroparticle (MP) contamination is the most important technological problem of vacuum arc deposition of coatings. The results of theoretical study of MP charging and dynamics in the near-substrate sheath are presented. The charge and dynamics of MP are governed by local parameters of ion and secondary electron emission fluxes in the sheath. It is shown that the maximum possible velocity of repelled MP increases with increasing substrate bias voltage. The effect of substrate biasing is seen to be larger for MPs emitted at small angles to the cathode plane of arc evaporator.